A versatile catalyst system for enantioselective synthesis of 2-substituted 1, 4-benzodioxanes. Issue 15 (20th March 2019) - Chong, Eugene; Qu, Bo; Zhang, Yongda; Cannone, Zachary P.; Leung, Joyce C.; Tcyrulnikov, Sergei; Nguyen, Khoa D.; Haddad, Nizar; Biswas, Soumik; Hou, Xiaowen; Kaczanowska, Katarzyna; Chwalba, Michał; et al.
Abstract : IrCl/BIDIME-dimer catalyzed hydrogenation is reported for enantioselective synthesis of 2-substituted 1, 4-benzodioxanes. Abstract : We report the synthesis of enantiomerically enriched 1, 4-benzodioxanes containing alkyl, aryl, heteroaryl, and/or carbonyl substituents at the 2-position. The starting 1, 4-benzodioxines were readily synthesized via ring closing metathesis using an efficient nitro-Grela catalyst at ppm levels. Excellent enantioselectivities of up to 99:1 er were obtained by using the versatile catalyst system [Ir(cod)Cl]2 /BIDIME-dimer in the asymmetric hydrogenation of 2-substituted 1, 4-benzodioxines. Furthermore, DFT calculations reveal that the selectivity of the process is controlled by the protonation step; and coordinating groups on the substrate may alter the interaction with the catalyst, resulting in a change in the facial selectivity.